Didelphys uterus: an interesting case report of pregnancy in a rare Mullerian anomaly - Pathan, Zeba H.; Chavan, Niranjan N.; Kampoowale, Shreya; Barkase, Akanksha; Kapote, Deepali S.; Sakhalkar, Ashwini S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Mullerian duct anomalies (MDAs) are congenital defects of the female genital system that arise from abnormal embryological development of the Mullerian ducts. A didelphys uterus, also known as a double uterus, is one of the least common amongst the MDAs. This report discussed a case of pregnancy with uterus didelphys. This patient was a 27-year-old primigravida with 34.2-week gestation with spontaneous conception who presented with decreased fetal movements. On examination patient had a non-communicating, thick vaginal septum extending from the introitus to the cervix was seen and two cervices one on each side of the septum were located. The patient underwent emergency lower segment caesarean section in view of foetal distress and doppler changes. Intra-operatively, evidence of didelphys uteri was seen. Intraoperative and post-operative period was uneventful. A fetus of 1790 gram was delivered, with APGAR 9/10. There were no renal anomalies on subsequent ultrasonography.